Computer‐aided drug design of small molecule inhibitors of the ERCC1‐XPF protein–protein interaction. (20th January 2020) - Gentile, Francesco; Elmenoufy, Ahmed H.; Ciniero, Gloria; Jay, David; Karimi‐Busheri, Feridoun; Barakat, Khaled H.; Weinfeld, Michael; West, Frederick G.; Tuszynski, Jack A.
Abstract: The heterodimer of DNA excision repair protein ERCC‐1 and DNA repair endonuclease XPF (ERCC1‐XPF) is a 5′–3′ structure‐specific endonuclease essential for the nucleotide excision repair (NER) pathway, and it is also involved in other DNA repair pathways. In cancer cells, ERCC1‐XPF plays a central role in repairing DNA damage induced by chemotherapeutics including platinum‐based and cross‐linking agents; thus, its inhibition is a promising strategy to enhance the effect of these therapies. In this study, we rationally modified the structure of F06, a small molecule inhibitor of the ERCC1‐XPF interaction ( Molecular Pharmacology, 84, 2013 and 12), to improve its binding to the target. We followed a multi‐step computational approach to investigate potential modification sites of F06, rationally design and rank a library of analogues, and identify candidates for chemical synthesis and in vitro testing. Our top compound, B5, showed an improved half‐maximum inhibitory concentration (IC50 ) value of 0.49 µM for the inhibition of ERCC1‐XPF endonuclease activit, and lays the foundation for further testing and optimization. Also, the computational approach reported here can be used to develop DNA repair inhibitors targeting the ERCC1‐XPF complex. Abstract : The ERCC1‐XPF is a DNA repair complex involved in chemotherapy drug resistance in cancer. We combined molecular dynamics simulations, virtual screening, and computer‐assisted medicinal chemistry to design small molecules targeting an XPF pocket essential for interacting with ERCC1, thus disrupting the active form of the ERCC1‐XPF dimer. Three compounds (B1, B2, and B5 ) significantly block ERCC1‐XPF incision activity in vitro and provide starting structures for further development of DNA repair inhibitors in combination cancer therapy.